Comparative Analysis of Student’s Perceptions in Accounting and Software Engineering Classes on Using Video Projects for Speaking - Dwi Prasetyo; Nunung Nurjati; Agung Pramujiono (Universitas Islam Negeri Palopo, 2026)
Speaking anxiety and lack of confidence remain major obstacles for Indonesian vocational high school students, particularly when they are required to perform English orally in front of the class. To address this issue, many teachers have begun to adopt video projects as an alternative assessment tool for speaking. This study investigates Grade XII Accounting and Software Engineering students’ perceptions of video projects as speaking assessment and examines how such projects help reduce speaking anxiety and increase confidence. Employing a comparative descriptive mixed-methods design, data were collected from 60 students at a private vocational high school in Surabaya through a Likert-scale questionnaire and semi-structured interviews with eight selected participants. The findings indicate that most students feel less anxious and more confident when completing video projects than when giving live presentations, mainly because they can rehearse, re-record, and control their performance before submission. Students also perceive video projects as an effective, engaging, and motivating assessment format that allows greater creativity and self-expression. However, some students still experience pressure related to pronunciation, video quality, and self-image, and they face practical challenges such as technical problems, limited devices, and difficulty finding a quiet place to record. Overall, the study concludes that video projects are a promising, student-centered alternative for assessing speaking in vocational contexts, provided that teachers offer sufficient pedagogical and technical support and balance video-based tasks with opportunities for spontaneous speaking.